Evaluating prevalence and risk factors of building-related symptoms among office workers: Seasonal characteristics of symptoms and psychosocial and physical environmental factors - Kenichi Azuma; Koichi Ikeda; Naoki Kagi; U Yanagi; Haruki Osawa (Komiyama Printing Co. Ltd, 2017)
Abstract Background Psychosocial and environmental factors at the workplace play a significant role in building-related symptoms (BRSs). Environmental factors change during summer cooling and winter heating using air-conditioning systems. Thus, significant risk factors in each season need to be clarified. Methods A nationwide cross-sectional study was conducted during summer in Japan and seasonal differences between summer and winter were evaluated. Self-administered questionnaires were distributed to 489 offices. Possible risk factors for BRSs associated with the work environment, indoor air quality, and job stressors were examined by multiple regression analyses. Results Among people having at least one BRS, the prevalence of BRSs in summer (27.8%) was slightly higher than that in winter (24.9%). High prevalence was observed for eye and nasal symptoms related to dryness and general symptoms related to psychological distress in both seasons. Analyses revealed that dryness of air was an important and significant risk factor associated with BRSs, and job stressors were significantly associated with general symptoms in both seasons. Conversely, humidity was a significant risk factor of general symptoms in summer (odds ratio, 1.20; 95% confidence interval, 1.02-1.43). Carpeting, recently painted walls, and unpleasant chemical odors in summer and noise, dust and dirt, and unpleasant odors such as body or food odors in both seasons were significant risk factors for BRSs. Conclusions Improvements in the physical environmental qualities in an office throughout the year are important along with the reduction in psychological distress related to work.